Application Planned Behavior in theory Predicting Junk Food Consumption among Female Students - tahere Dehdari; maryam Chegni; lale Dehdari (Zanjan University of Medical Sciences and Health Services, 2013)
Background and Objectives: There are high tendency among adolescence for consuming junk foods. The aim of this study was to predict the junk food consumption based on the theory of planned behavior among female student in Kermanshah, 2011. Material and Methods: In this descriptive-analytical study, 207 female students studying in middle schools of Kermanshah were selected using multi stage sampling method. The students filled out a self-structured questionnaire provided based on the theory of planned behavior. Statistical analysis of the data was done in the SPSS using correlation analysis, regression analysis and One-way ANOVAs. Results:Most of the students had consumed junk foods. The findings showed that behavioral intention, perceived behavioral control and subjective norms could predict 44 percent of the variation in junk food consumption behavior. Among constructs of the theory of planned behaviors, only perceived behavioral control was able to predict 44 percent of the variation in junk food consumption intention. Conclusion: Regarding more consumption of junk foods than nutrient foods and fruits among students, it is essential to conduct educational interventions based on theories of behavioral sciences. students is high and various interventions based on behavioral change theories (for example, the theory of planned behavior) it is necessary.